Evaluation of Some Proteins as Potential Markers in Different Durations of Diabetic Patients Type 2 - Sami, Sarah Sameer; Taha , Ekhlass M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Type 2 diabetic mellitus (T2DM) is growing rapidly around the world, due in large part to significant changes in the modern human lifestyle. T2DM and its complications are affected by a complex interplay of genetic, life course, ecological, cultural, socioeconomic, cognitive-psychological-behavioral, and access to care factors that influence regional variations in disease burden and care quality by gender. This study aims to investigate the role of laminin subunit alpha 2 (LAMA2), mixed lineage leukemia 4 (MLL4), plexin domain containing 2 (PLXDC2), and Protein Z (PORZ) as potential biomarkers for T2DM at different durations of the disease. These biomarkers were assessed using an enzyme-linked immunosorbent assay. While biochemical parameters (FSG) and lipid profiles were measured spectrophotometrically. HbA1C using HPLC. The volunteer individuals were subdivided into five groups: group I: DM with duration of disease less than 1 year, group II: DM with duration of disease from 1-5 years, group III: DM with duration of disease from 5-10 years, group IV: DM with duration of disease more than 10 years, group V: healthy control. Results showed a significant difference among the studied groups in LAMA2 and PLXDC2. In contrast, no significant difference was observed in MLL4 and POR Z. It has been concluded that LAMA2 and PLXDC2 are involved in the duration of the disease